2016
DOI: 10.1259/bjr.20150897
|View full text |Cite
|
Sign up to set email alerts
|

Radiation risk of breast screening in England with digital mammography

Abstract: Objective: To estimate the risks and benefits of breast screening in terms of number of deaths due to radiationinduced cancers and the number of lives saved owing to modern screening in the National Health Service Breast Screening Programme (NHSBSP) in England. Methods: Radiation risk model, patient dose data and data from national screening statistics were used to estimate the number of deaths due to radiation-induced breast cancers in the NHSBSP in England. Dose and dose effectiveness factors (DDREFs) equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…1), suggesting that they are more at risk compared to older patients (median age is 44.0 years). The mean tube voltage was comparable with previous studies and breast thickness (Baek et al, 2017, Warren et al, 2016, Hauge et al, 2014, Dance et al, 2009). The mean ESAK (mGy) and MDG (mGy) were 4.4 ± 1.1 and 1.1 ± 0.3, respectively.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…1), suggesting that they are more at risk compared to older patients (median age is 44.0 years). The mean tube voltage was comparable with previous studies and breast thickness (Baek et al, 2017, Warren et al, 2016, Hauge et al, 2014, Dance et al, 2009). The mean ESAK (mGy) and MDG (mGy) were 4.4 ± 1.1 and 1.1 ± 0.3, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Mammographic image quality and MGD depend on imaging technique and the radiographic system used. The patient radiation dose per mammographic examination is lower compared to the previous published researches (Warren et al, 2016, Pasicz et al, 2016, Fartaria et al, 2016, Ślusarczyk-Kacprzyk et al, 2016, Soliman and Bakkari, 2015, Hauge et al, 2014, Al-Kafi et al, 2009, Dance et al, 2009, Smathers et al, 2007, Kruger and Schueler, 2001) (Fig. 2).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The impact of overdiagnosis on radiation exposure is extremely difficult to estimate. It has been evaluated that the mean glandular dose for screening mammography ranges between 3 and 10 mGy and it is mainly influenced by the number of views acquired, the technology used and by patient-related factors [57,58]. Despite the radiation exposure level, it has been demonstrated that the number of deaths caused by radiation-induced cancers is around 125-208 time smaller than the lives saved owing to screening [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The exposure from mammography poses an additional risk to induce tumors by ionizing radiation. Several papers have examined and estimated the risk arising from such screening programs and compared with the benefit 24 .…”
Section: Introductionmentioning
confidence: 99%